Delayed Security Price Adjustments to Financial Analysts' Forecasts of Annual Earnings - Elgers, Pieter T.; Lo, May H.; Pfeiffer, Ray J. (The Accounting Review, 2001)
This paper documents that the weighting of analysts' annual earnings forecasts implicit in security prices is lower than the historical relation between financial analysts' forecasts and realized earnings. Short positions in securities in the bottom decile and long positions in the top decile of the crosssectional distribution of analysts' early-in-the-year earnings forecasts generate significant hedge-portfolio returns in the year after portfolio formation. This delayed price response is more pronounced for firms with relatively low analyst coverage, consistent with the premise that low financial analyst coverage is associated with a variety of factors that impede the information efficiency of the security market. The hedge-portfolio returns concentrate in the months of subsequent quarterly earnings announcements, suggesting that the delayed security price adjustments reflect the market's failure to incorporate information in analysts' forecasts about future earnings, rather than deficiencies in our conditional expectations of security returns.